Attitude and pregnancy planning of the women reproductiove of age not associated - Sri Ayu Candra A. Misali; Wahyuningsih Wahyuningsih; Taufik Rahman (Alma Ata University Press, 2021)
Background: The pregnancy planning is an important strategy to improve the children quality to be born and efforts to decrease maternal and infant mortality. The number of maternal mortality in Yogyakarta in 2018 was 36 cases. Most cases occurred in Bantul District as 14 cases. Meanwhile, the infant mortality case was 313 cases in 2017. The highest infant mortality case in Bantul District was 108 cases. Attitude is a feeling, supporting and not supporting on something. The Government Regulation of Republic of Indonesia Number 87 of 2014 concerning Population Development and Family Development, Family Planning and Family Information Systems stated that Family Planning is an effort to regulate the birth, the ideal distance and age to give birth, regulate pregnancy through promotion, protection, and assistance related to reproductive rights to realize a quality family. Having 2 children is the realization of one of the criteria for a quality family in the ideal number of children program. Objectives: This study aimed to determine the correlation between attitudes and behavior of pregnancy planning among women of childbearing age in Bantul District. Methods: This research used correlational quantitative research using cross sectional approach design. The sampling collection technique used non-probability sampling with purposive sampling. The samples was 71 respondents with inclusion criteria, namely women of childbearing aged <20 - > 35 years, located in Bantul district, had a legal spouse, owned and could operate a gadget. The validity test was conducted with SPSS Pearson Correlation with a significance level of 10% and Kendall's tau to determine the relationship between variables. Results: There is no correlation between attitudes towards pregnancy planning of women of childbearing age with P value of 0.052 > 0.05 (P Value ≤ 0.05). Conclusion: The characteristics of the most respondents were women aged 35 - 40 years, the last education was senior high school, the income was 0 - Rp 500.000,00 and the number of children was 2. The attitude of the respondent was mostly positive, while the most respondents who plan the pregnancy were ambivalent and the respondents who are not planning the pregnancy more than women who are planning a pregnancy.